Electrode, secondary battery, battery pack, and vehicle

By using polymer fibers and inorganic solid particles in the positive and negative active material-containing layers of secondary batteries, the problem of battery performance degradation during charge and discharge cycles and low temperature environments is solved, and longer cycle life and higher efficiency are achieved. Discharge rate performance.

CN119361922APending Publication Date: 2025-01-24KK TOSHIBA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311372670.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-09-19
Filing Date
2018-08-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing all-solid secondary batteries have increased ion conduction resistance and increased interface resistance during the charge and discharge cycle, resulting in a decrease in cycle life and discharge rate performance, especially in low-temperature environments.

Method used

The positive and negative electrode active material containing layers containing polymer fibers and inorganic solid particles are used to retain the electrolyte through the fine mesh space formed by the polymer fibers, reduce ion conduction resistance, and improve lithium ion conductivity through the selection of inorganic solid particles.

Benefits of technology

The charge-discharge cycle life, discharge rate performance and low-temperature performance of the secondary battery are significantly improved, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004506855930000351
    Figure BDA0004506855930000351
  • Figure BDA0004506855930000361
    Figure BDA0004506855930000361
  • Figure BDA0004506855930000371
    Figure BDA0004506855930000371
Patent Text Reader

Abstract

The invention relates to an electrode, a secondary battery, a battery pack, and a vehicle. According to one embodiment, an electrode including active material particles, polymer fibers, and inorganic solid particles is provided. The polymer fibers have an average fiber diameter of 1 nm or more and 100 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application number 201880003375.X, application date August 21, 2018, and invention name “Electrode, Secondary Battery, Battery Pack and Vehicle”. Technical Field

[0002] Embodiments relate to a positive electrode, an electrode, a secondary battery, a battery pack, and a vehicle. Background Art

[0003] Non-aqueous electrolyte batteries containing lithium metal, lithium alloy, lithium compound or carbonaceous material in the negative electrode are expected to be high energy density batteries. Therefore, research and development of such batteries are actively carried out. 1 / 3 Co 1 / 3 Mn 1 / 3 Lithium ion batteries with a positive electrode of LiO2 or LiMn2O4 and a negative electrode containing a carbonaceous material that absorbs and releases lithium have been widely put into practical use. In addition, research has been conducted on metal oxides or alloys that replace carbonaceous materials in the negative electrode.

[0004] Especially, when being carried in vehicles such as automobiles, from the perspective of cycle performance under high temperature environment, long-term reliability of high output power, and safety, materials with excellent chemical and electrochemical stability, strength, and corrosion resistance are required for the constituent materials of the negative electrode. And then, even in cold regions, high performance is required, and high output power performance and long life performance under low temperature environment are required. On the other hand, as electrolyte, from the perspective of improving safety performance, the development of solid electrolytes, non-volatile electrolytes, and inflammable electrolytes is being carried out. However, the use of solid electrolytes, non-volatile electrolytes, or inflammable electrolytes is not yet practical due to the reduction of discharge rate performance, low temperature performance, and long life performance.

[0005] In the development of all-solid secondary batteries, research and development are being conducted to improve the ion conductivity of oxide solid electrolytes and sulfide solid electrolytes, but the ion conduction resistance, reaction resistance and electrode / solid electrolyte interface resistance inside the electrode become larger, and there are problems in discharge performance and low temperature performance. In addition, during the charge and discharge cycle, the blockage of the ion conduction path inside the electrode caused by electrode expansion and contraction leads to increased resistance and reduced electrode / solid electrolyte bonding, increased electrode / solid electrolyte interface resistance, and significant reductions in cycle life performance and discharge rate performance. Due to such issues, the practical application of all-solid secondary batteries using solid electrolytes has become difficult.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 5110565

[0009] Patent Document 2: Japanese Patent No. 6020892 Summary of the invention

[0010] Problems to be solved by the invention

[0011] An object of the embodiment is to provide a secondary battery having excellent charge and discharge cycle life, discharge rate performance, and low temperature performance, a positive electrode and an electrode capable of realizing the secondary battery, a battery pack including the secondary battery, and a vehicle including the battery pack.

[0012] Means for solving problems

[0013] According to an embodiment, a positive electrode is provided, comprising a positive electrode active material containing layer, the positive electrode active material containing layer comprising: positive electrode active material particles, polymer fibers, and inorganic solid particles. The average fiber diameter of the polymer fibers is 1 nm or more and 100 nm or less.

[0014] According to an embodiment, an electrode is provided, comprising an active material containing layer, the active material containing layer comprising active material particles, polymer fibers, and inorganic solid particles. The average fiber diameter of the polymer fibers is 1 nm or more and 100 nm or less.

[0015] In addition, according to another embodiment, a secondary battery including the positive electrode or the electrode of the embodiment is provided.

[0016] According to another embodiment, there is provided a battery pack including the secondary battery of the embodiment.

[0017] According to another embodiment, a vehicle including the battery pack of the embodiment is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a partially cut-away cross-sectional view of a secondary battery according to an embodiment.

[0019] Figure 2 For Figure 1 Side view of a battery.

[0020] Figure 3 This is a cross-sectional view of the secondary battery according to the embodiment cut along a direction perpendicular to the direction in which the terminals extend.

[0021] Figure 4 for Figure 3 An enlarged cross-sectional view of section A.

[0022] Figure 5 It is a cross-sectional view showing another example of the secondary battery according to the embodiment.

[0023] Figure 6 It is a perspective view showing an example of a battery module including a secondary battery according to an embodiment.

[0024] Figure 7 An exploded perspective view of a battery pack according to an embodiment.

[0025] Figure 8 To express Figure 7 Block diagram of the battery pack circuit.

[0026] Fig. 9 It is a schematic diagram showing an example of a vehicle equipped with the secondary battery according to the embodiment.

[0027] Fig.10 It is a diagram schematically showing another example of the vehicle according to the embodiment. DETAILED DESCRIPTION

[0028] (First Embodiment)

[0029] According to a first embodiment, a positive electrode including positive electrode active material particles, polymer fibers, and inorganic solid particles is provided. The average fiber diameter of the polymer fibers is 1 nm or more and 100 nm or less.

[0030] As for the positive electrode active material particles, the positive electrode active material particles with high potential such as lithium nickel cobalt manganese composite oxide particles and lithium phosphorus oxide particles with an olivine structure that absorb and release lithium ions have large expansion and contraction when absorbing and releasing lithium ions. Therefore, the liquid electrolyte (electrolyte) and gel electrolyte retained in the positive electrode may sometimes seep out of the positive electrode due to the expansion and contraction of the positive electrode active material.

[0031] The polymer fiber with an average fiber diameter of 1 nm or more and 100 nm or less is easily dispersed in the positive electrode to form a fine mesh space because the fiber diameter is nanometer-sized. As a result, the electrolyte such as a liquid electrolyte and a gel electrolyte is loaded or maintained on the polymer fiber, so that the cutoff of ion conduction accompanied by the expansion and contraction of the positive electrode active material can be suppressed, and the ion conduction resistance in the positive electrode can be reduced. Therefore, the secondary battery with the positive electrode can improve the charge and discharge cycle life, discharge rate performance and low temperature performance.

[0032] By including cellulose fibers in the polymer fibers, the aspect ratio of the polymer fibers can be greatly increased, for example, to be greater than 100 and less than 10,000, thereby promoting the formation of fine mesh-like spaces generated by the polymer fibers. As a result, the electrolyte is further inhibited from detaching from the positive electrode, thereby further reducing the ion conduction resistance in the positive electrode. Therefore, the secondary battery with the positive electrode can further improve the charge and discharge cycle life, discharge rate performance and low temperature performance.

[0033] By containing at least one selected from Al2O3, TiO2, ZrO2 and a phosphoric acid compound in the inorganic solid particles, these inorganic solid particles can conduct lithium ions in the absence of a solvent, thereby promoting ion conduction in the positive electrode.

[0034] Preferably, the phosphate compound contains: a NASICON-type structure and a Li 1+y Al x M 2-x A compound represented by (PO4)3 (M is at least one element selected from Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1). It is believed that at the interface of liquid, gel electrolyte, inorganic solid particles and positive electrode active material particles maintained in a fine mesh space formed by polymer fibers, the lithium ion concentration is increased without being affected by solvation, and high-speed lithium ion conduction is manifested, which reduces the ion conduction resistance in the positive electrode and the resistance at the interface of the positive electrode active material particles.

[0035] By setting the polymer fiber content to be greater than 0.2 wt % and less than 5 wt % and the inorganic solid particle content to be greater than 0.5 wt % and less than 10 wt %, the lithium ion conduction resistance and electron conduction resistance of the positive electrode can be reduced while maintaining a high positive electrode density.

[0036] In addition, a secondary battery including a positive electrode, a negative electrode including an oxide containing titanium, and an electrolyte can achieve excellent charge and discharge cycle life, discharge rate performance, and low temperature performance.

[0037] By including at least one selected from spinel-structured lithium titanium oxide, monoclinic titanium oxide, and niobium titanium oxide in the titanium-containing oxide, the safety of the secondary battery can be improved.

[0038] The positive electrode is further described below.

[0039] The positive electrode comprises a positive electrode current collector and a positive electrode active material containing layer loaded on at least one main surface, i.e., one surface or both surfaces, of the current collector. The positive electrode active material containing layer comprises positive electrode active material particles that absorb, store and release lithium ions, polymer fibers having an average fiber diameter of 1 nm or more and 100 nm or less, and inorganic solid particles. In addition, the positive electrode active material containing layer may further comprise a conductive agent and a binder.

[0040] Aluminum foil or aluminum alloy foil can be used in the positive electrode current collector. The purity of aluminum foil and aluminum alloy foil can be made 99% or more. The upper limit of purity is 100% (pure aluminum). The more preferred aluminum purity is 99% or more and 99.99% or less. If it is within this range, the high temperature cycle life degradation caused by the dissolution of impurity elements can be reduced.

[0041] Aluminum alloy is preferably an alloy containing one or more elements selected from iron, magnesium, zinc, manganese and silicon in addition to aluminum. For example, Al-Fe alloys, Al-Mn alloys and Al-Mg alloys can obtain a higher strength than aluminum. On the other hand, it is preferred to make the content of transition metals such as nickel and chromium in aluminum and aluminum alloys less than 100 wtppm (including 0 wtppm). For example, for Al-Cu alloys, the strength is improved, but there is a tendency for the corrosion resistance to decrease.

[0042] Examples of positive electrode active materials include lithium manganese composite oxides, lithium cobalt composite oxides, lithium nickel composite oxides, lithium nickel cobalt composite oxides, lithium cobalt aluminum composite oxides, lithium nickel aluminum composite oxides, lithium nickel cobalt manganese composite oxides, spinel-structured lithium manganese nickel composite oxides, lithium manganese cobalt composite oxides, olivine-structured lithium-containing phosphate compounds, fluorinated iron sulfate, lithium nickel cobalt manganese composite oxides, etc. The type of positive electrode active material that can be used is one or more than two.

[0043] Examples of the lithium manganese composite oxide include Li x Mn2O4(0<x≤1), Li x MnO2(0<x≤1) etc.

[0044] Examples of lithium cobalt composite oxides include Li x CoO2(0<x≤1) etc.

[0045] Examples of lithium nickel aluminum composite oxides include Li x Ni 1-y Al y O2(0<x≤1, 0<y≤1), etc.

[0046] Examples of lithium nickel cobalt composite oxides include Li x Ni 1-y-z Co y Mn z O2 (0<x≤1, 0<y≤1, 0≤z≤1, 0<1-yz<1), etc.

[0047] Examples of lithium manganese cobalt composite oxides include Li x Mn y Co 1-y O2 (0<x≤1, 0<y<1), etc.

[0048] Examples of the lithium manganese nickel composite oxide having a spinel structure include Li x Mn 2-y Ni y O4 (0<x≤1, 0<y<2), etc.

[0049] Examples of the lithium-containing phosphate compound having an olivine structure include Li x FePO4(0<x≤1), Li x Fe 1-y Mn y PO4(0<x≤1, 0≤y≤1), Li x CoPO4(0<x≤1), Li x MnPO4(0<x≤1) etc.

[0050] Examples of ferric sulfate fluoride include Li x FeSO4F(0<x≤1), etc.

[0051] Examples of lithium nickel cobalt manganese composite oxides include Li x Ni 1-y-z Co y Mn z O2 (0<x≤1.1, 0<y≤0.5, 0<z≤0.5, 0<1-yz<1), etc.

[0052] If the above positive electrode active materials are used, a high positive electrode voltage can be obtained. Among them, if lithium nickel aluminum composite oxide, lithium nickel cobalt manganese composite oxide, lithium manganese cobalt composite oxide are used, the reaction with the electrolyte in a high temperature environment can be suppressed, and the battery life can be greatly improved. x Ni 1-y-z Co y Mn z The lithium nickel cobalt manganese composite oxide represented by O2 can obtain excellent high-temperature durability life.

[0053] The positive electrode active material particles may be in the form of primary particles or secondary particles formed by aggregation of primary particles. In addition, the primary particles and the secondary particles may be mixed together.

[0054] The average primary particle size of the positive electrode active material particles can be set to 0.05 μm or more and 3 μm or less.

[0055] In addition, the average secondary particle size of the positive electrode active material particles can be set to 3 μm or more and 20 μm or less.

[0056] The conductive agent can improve electron conductivity and suppress contact resistance with the current collector. Examples of the conductive agent include acetylene black, carbon black, and graphite.

[0057] The binder can bind the active material and the conductive agent. Examples of the binder include polymers such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, styrene butadiene rubber, and carboxymethyl cellulose (CMC). The binder can impart flexibility to the active material-containing layer containing polymer fibers. PVdF and styrene butadiene rubber are excellent in improving flexibility.

[0058] The reason for limiting the average fiber diameter of the polymer fiber is explained. If the average fiber diameter exceeds 100nm, it becomes difficult to finely distribute the polymer fiber in the positive electrode. In addition, since the specific surface area of ​​the polymer fiber is insufficient, the amount of electrolyte that can be retained in the polymer fiber becomes less. As a result, the low temperature performance or discharge rate performance of the battery is reduced. It is preferred that the average fiber diameter is small, but if it is less than 1nm, the dispersion of the fibers in the electrode becomes insufficient, and the fibers can no longer evenly retain the electrolyte. The more preferred range of the average fiber diameter is greater than 5nm and less than 50nm.

[0059] It is preferred that the content of the polymer fiber in the positive electrode active material containing layer is 0.2% by weight or more and 5% by weight or less. If the content of the polymer fiber exceeds 5% by weight, the content of the components other than the polymer fiber becomes relatively less, so sometimes the density of the positive electrode decreases. In addition, if the content of the polymer fiber is less than 0.2% by weight, the effect of the polymer fiber having an average fiber diameter of 1 nm or more and 100 nm or less cannot be obtained, and sometimes the charge and discharge cycle life, discharge rate performance, and low temperature performance are reduced. The more preferred range of the content is 0.3% by weight or more and 2% by weight or less.

[0060] The polymer fiber is preferably cellulose fiber (cellulose nanofiber). Cellulose fiber has a nanometer-sized fiber diameter with an average fiber diameter of 1 nm to 100 nm, and a very large aspect ratio (100 to 10,000), which can firmly hold the liquid electrolyte in the fine mesh space of the fiber.

[0061] The inorganic solid particles are preferably at least one selected from Al2O3, TiO2, ZrO2 and phosphoric acid compounds. In addition, as phosphoric acid compounds, for example, AlPO4, Li3PO4, a NASICON-type structure and composed of Li 1+y Al x M 2-x Phosphoric acid compounds represented by (PO4)3 (M is at least one element selected from Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1) etc. having a NASICON structure and consisting of Li 1+y Al x M 2-xThe phosphoric acid compound represented by (PO 4 ) 3 has excellent stability in air and obtains high lithium ion conductivity.

[0062] The average particle size of the inorganic solid particles can be less than 1 μm. The more preferred range is 0.01 μm or more and 1 μm or less, and the further preferred range is 0.05 μm or more and 0.6 μm or less. If it is within this range, the lithium ion conductivity in the positive electrode is improved, so the resistance of the positive electrode becomes smaller. By compounding the polymer fibers and the inorganic solid particles, high-speed ion conductivity can be maintained even in the positive electrode with large expansion and contraction. In particular, at the interface between the liquid, gel electrolyte and the inorganic solid particles with an average particle size of less than 1 μm and the high-potential positive electrode active material particles maintained in the fine mesh space formed by the polymer fibers, it is believed that the lithium ion concentration that is not affected by the solvation increases, and high-speed lithium ion conduction appears, which reduces the ion conduction resistance in the electrode and the resistance of the positive electrode active material interface.

[0063] Preferably, the content of the inorganic solid particles in the positive electrode active material containing layer is 0.5% by weight or more and 10% by weight or less. If the content of the inorganic solid particles exceeds 10% by weight, the content of the components other than the inorganic solid particles decreases relatively, so the density of the positive electrode is reduced sometimes. In addition, if the content of the inorganic solid particles is less than 0.5% by weight, the effect of the inorganic solid particles cannot be obtained, and the charge and discharge cycle life, discharge rate performance and low temperature performance are reduced sometimes. The more preferred range of the content is 1% by weight or more and 6% by weight or less.

[0064] The positive electrode may contain an electrolyte. In addition, as a polymer for gelling the electrolyte in the positive electrode, for example, a polymer gelled with a carbonate can be cited. Examples of such polymers include polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), polymethyl methacrylate, etc. The gel polymer electrolyte using polyacrylonitrile has high ion conductivity, and the discharge performance and low temperature performance are improved, so it is preferred. The proportion of the gel polymer electrolyte in the positive electrode active material containing layer is preferably 1% by weight or more and 10% by weight or less. If it deviates from this range, the low temperature performance and discharge performance are sometimes reduced.

[0065] The components that may be contained in the positive electrode described above, such as the positive electrode active material, the conductive agent, the binder, the polymer fiber, the inorganic solid particles, the polymer body, etc., may be one kind or two or more kinds.

[0066] Regarding the proportion of the positive electrode active material, the conductive agent and the binder, it is preferred that the positive electrode active material is 80% by weight or more and 95% by weight or less, the conductive agent is 3% by weight or more and 18% by weight or less, and the binder is 2% by weight or more and 7% by weight or less. Regarding the conductive agent, by being 3% by weight or more, the above-mentioned effect can be exerted, and by being 18% by weight or less, the decomposition of the non-aqueous electrolyte on the surface of the conductive agent under high temperature storage can be reduced. Regarding the binder, by being 2% by weight or more, sufficient electrode strength is obtained, and by being 7% by weight or less, the insulating portion of the electrode can be reduced.

[0067] The preferred mixing ratio of the positive electrode active material, conductive agent, binder, polymer fiber, and inorganic solid particles is in the range of 80 to 95 wt % of the positive electrode active material, 1 to 8 wt % of the conductive agent, 0.5 to 3 wt % of the binder, 0.2 to 5 wt % of the polymer fiber, and 0.5 to 10 wt % of the inorganic solid particles.

[0068] The positive electrode is prepared, for example, by suspending a positive electrode active material, a conductive agent, and a binder in an appropriate solvent, applying the suspension to a positive electrode collector, drying, and pressing. The positive electrode pressing pressure is preferably in the range of 0.15 tons / mm to 0.3 tons / mm. If it is in this range, the adhesion (peel strength) between the positive electrode active material containing layer and the positive electrode collector such as aluminum foil is improved, and the elongation of the positive electrode collector foil is preferably less than 20%.

[0069] The positive electrode is prepared, for example, by dispersing particles of a positive electrode active material, polymer fibers, inorganic solid particles, a conductive agent, and a binder in a solvent, applying the obtained dispersion to a current collector, drying, and pressing (for example, heating and pressing). Alternatively, particles of a positive electrode active material, a conductive agent, and a binder are dispersed in a solvent to obtain a first dispersion. In addition, polymer fibers and inorganic solid particles are dispersed in a solvent to obtain a second dispersion. After applying the first dispersion to the current collector, the second dispersion is applied to the layer of the first dispersion on the current collector. Next, the positive electrode is obtained by drying and pressing (for example, heating and pressing). Application of the dispersion to the current collector is carried out, for example, using a sprayer, a die-coating applicator, or the like.

[0070] The following describes a method for determining the content of polymer fibers in the positive electrode active material containing layer. The positive electrode active material containing layer peeled from the positive electrode current collector is crushed using a mortar, etc., and the obtained crushed material is dispersed in water, and the polymer fibers are separated by using the specific gravity difference. The polymer fibers in the supernatant are dried at 100°C for 12 hours, and the weight of the polymer fibers is measured to determine the content of the polymer fibers in the positive electrode active material containing layer.

[0071] The polymer fibers whose weight was measured by the above method were observed with a scanning electron microscope (SEM) at a magnification of 10,000 times, and the widths at 25%, 50%, and 75% of the total length of the polymer fibers in the field of view were measured. The average of the measured width values ​​was taken as the average fiber diameter. The measurement was performed on all polymer fibers present in the field of view.

[0072] The following describes a method for determining the content of solid inorganic particles in the positive electrode active material containing layer. The positive electrode active material containing layer that has been subjected to the electrolyte removal treatment described later is crushed using a mortar or the like, the crushed material obtained is dispersed in water, and the polymer fibers and the conductive agent are separated using the specific gravity difference. The polymer fibers and the conductive agent in the supernatant are removed. The precipitate is washed with dimethyl carbonate to remove the binder. Next, it is dried, and for the obtained powder, the particle size distribution data is obtained using the laser diffraction described later. Based on the obtained particle size distribution data, the content of solid inorganic particles in the positive electrode active material containing layer is calculated.

[0073] The average primary particle size of the positive electrode active material particles and the solid inorganic particles is measured by the following method. Using a laser diffraction distribution measuring device (Shimadzu SALD-300 or a device having an equivalent function), first, add about 0.1 g of the sample and a surfactant and 1 to 2 mL of distilled water to a beaker, stir thoroughly, inject into a stirring water tank, measure 64 times of photometric distribution at 2 second intervals, analyze the particle size distribution data, and measure using such a method.

[0074] When confirming the average fiber diameter of the polymer fiber for the positive electrode contained in the secondary battery, the positive electrode is removed from the secondary battery by the following method. The secondary battery is decomposed in a glove box filled with argon gas, and the positive electrode is taken out. The positive electrode active material containing layer is peeled off from the positive electrode collector of the positive electrode taken out. Next, the positive electrode active material containing layer is washed with dimethyl carbonate and the electrolyte is removed, and then dried. Then, the average fiber diameter of the polymer fiber is confirmed.

[0075] The positive electrode of the first embodiment described above comprises positive electrode active material particles that absorb, store and release lithium ions, polymer fibers with an average fiber diameter of 1 nm or more and 100 nm or less, and inorganic solid particles. This can reduce the ion conduction resistance of the positive electrode. Therefore, the secondary battery with the positive electrode can improve the charge and discharge cycle life, discharge rate performance and low temperature performance.

[0076] (Second Embodiment)

[0077] The secondary battery of the second embodiment includes a positive electrode, a negative electrode and an electrolyte. The positive electrode of the first embodiment can be used in the positive electrode. In addition, the secondary battery can have an outer casing member for accommodating the positive electrode, the negative electrode and the electrolyte. In the secondary battery, an electrolyte-containing layer can be configured between the positive electrode and the negative electrode.

[0078] The electrolyte, the negative electrode, the electrolyte-containing layer, and the exterior member are described below.

[0079] 1) Electrolytes

[0080] Examples of the electrolyte include liquid electrolytes, gel electrolytes, solid electrolytes, and composite electrolytes.

[0081] The liquid electrolyte contains an electrolyte salt such as a lithium salt and an organic solvent that dissolves the electrolyte salt. The gel electrolyte contains an electrolyte salt such as a lithium salt, an organic solvent that dissolves the electrolyte salt, and a polymer as a gelling agent. The solid electrolyte contains an oxide or sulfide having lithium ion conductivity. The composite solid electrolyte contains inorganic solid particles (hereinafter referred to as the second inorganic solid particles) and a polymer containing lithium ions and an organic solvent, and is a composite of the second inorganic solid particles and the gel electrolyte. The composite electrolyte has high ion conductivity and is preferred.

[0082] As long as the polymer can gel the organic solvent containing lithium ions, there is no particular limitation, and both chemical gelling agents and physical gelling agents can be used. For example, polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), polymethyl methacrylate and other polymers that can be gelled with carbonates can be listed. A gelled polymer electrolyte is generated by composite carbonates with polymers, thereby improving the ion conductivity of the composite electrolyte. The gel-like polymer electrolyte containing polyacrylonitrile has high ion conductivity, and the discharge performance and low temperature performance are improved, so it is preferred. The proportion of polymer in the composite electrolyte is preferably more than 1% by weight and less than 10% by weight. If it is out of this range, the low temperature performance and discharge performance are likely to decrease. The type of polymer can be one or more than two.

[0083] In order to improve the mechanical strength, the composite electrolyte may contain a binder. Examples of binders include polyvinylidene fluoride (PVdF) and acrylic binders. The binder may be added in a range of 0 to 5% by weight. If this range is exceeded, the ion conductivity of the electrolyte may be reduced, and the discharge performance may be reduced.

[0084] The composite electrolyte may contain the polymer fibers contained in the positive electrode of the first embodiment. It is preferred that the content of the polymer fibers in the composite electrolyte is in the range of 0.1% by weight or more and 10% by weight or less. If it is in this range, the mechanical strength of the composite electrolyte layer increases, the thickness can be thinned to 10 μm, and the internal resistance of the battery can be reduced while greatly reducing internal short circuits and self-discharge. Furthermore, the bonding force between the positive and negative electrodes and the composite electrolyte is increased, and they will not deteriorate during the charge and discharge cycle, and the increase in interface resistance is suppressed, which greatly improves the cycle life performance.

[0085] The second inorganic solid particles may be inorganic particles having no lithium ion conductivity or low lithium ion conductivity, or may be inorganic solid electrolytes having high lithium ion conductivity. The second inorganic solid particles may be used in one or more types.

[0086] Examples of inorganic particles having no lithium ion conductivity or low lithium ion conductivity include lithium aluminum oxides (e.g., LiAlO2, Li x Al2O3, wherein 0<x≤1), lithium silicon oxide, lithium zirconium oxide.

[0087] An example of an inorganic solid electrolyte having lithium ion conductivity includes a garnet-type oxide solid electrolyte. Garnet-type oxide solid electrolytes have the advantages of high lithium ion conductivity and reduction resistance and a wide electrochemical window. 5+x A x La 3-x M2O 12 (A is at least one element selected from Ca, Sr and Ba, M is Nb and / or Ta, and x is preferably in the range of 0.5 or less (including 0).), Li3M 2-x L2O 12 (M contains Nb and / or Ta, L contains Zr, and x is preferably in the range of 0.5 or less (including 0)), Li 7-3x Al x La3Zr3O 12 (x is preferably in the range of 0.5 or less (including 0)), Li7La3Zr2O 12 Among them, Li 6.25 Al 0.25 La3Zr3O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 6.4 Ln3Z 1.6 Ta 0.6 O 12 、Li7La3Zr2O 12The ion conductivity is high and the electrochemical stability is good, so the discharge performance and cycle life performance are excellent. In addition, it has 10 to 500m 2 / g (preferably 50 to 500 m 2 Microparticles having a specific surface area of ​​1000 Å / g) have the advantage of being chemically stable to organic solvents.

[0088] In addition, examples of inorganic solid electrolytes having lithium ion conductivity include lithium phosphate solid electrolytes having a NASICON structure. Lithium phosphate solid electrolytes having a NASICON structure are highly stable to water and are therefore difficult to dissolve in water. Examples of lithium phosphate solid electrolytes having a NASICON structure include Li 1+y Al x M 2-x (PO4)3, wherein M is one or more elements selected from Ti, Ge, Sr, Sn, Zr and Ca. x and y are 0≤x≤1, 0≤y≤1. As preferred examples, Li 1+x Al x Ge 2-x (PO4)3、Li 1+x Al x Zr 2-x (PO4)3、Li 1+x Al x Ti 2-x (PO4)3. In each of them, x is preferably in the range of 0 or more and 1 or less. In addition, each of the exemplified solid electrolytes has high ion conductivity and high electrochemical stability. Since they are electrochemically stable, they have excellent discharge performance and cycle life performance, and have the ability to be further micronized to 10 to 500 m 2 The large specific surface area of ​​1.3777 Å / g is chemically stable to organic solvents. The preferred particle size (diameter) is 0.01 μm or more and 1 μm or less. If it is within this range, the ion conductivity in the composite electrolyte is improved, so the discharge performance and low temperature performance are improved. More preferably, it is 0.05 μm or more and 0.6 μm or less.

[0089] The proportion of inorganic solid particles in the composite electrolyte can be made to be more than 85% by weight and less than 98% by weight. By making it more than 85% by weight, the increase of self-discharge accompanied by internal short circuit caused by the reduction of the strength of the electrolyte can be avoided. In addition, by making it less than 98% by weight, the reduction of discharge performance and the reduction of low-temperature performance caused by the rapid reduction of the ion conductivity of the electrolyte can be avoided.

[0090] As the inorganic solid electrolyte having lithium ion conductivity, both a lithium phosphate solid electrolyte having a NASICON structure and an oxide solid electrolyte having a garnet structure can be used.

[0091] The organic electrolyte solution containing lithium ions is prepared by, for example, dissolving a lithium salt in a solvent including an organic solvent.

[0092] Examples of lithium salts include LiPF6, LiClO4, LiBF4, LiCF3SO3, LiN(FSO2)2, LiN(CF3SO2)2, etc. At least one lithium salt selected from LiPF6, LiBF4 and LiN(FSO2)2 improves ion conductivity and discharge performance.

[0093] The organic solvent preferably comprises carbonates. In the example of carbonates, as cyclic carbonate, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) can be listed, as linear carbonate, diethyl carbonate (DEC), ethyl methyl carbonate (MEC), dimethyl carbonate (DMC) can be listed. If propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC) are used, low temperature performance improves.

[0094] In addition, the organic solvent may contain other solvents besides carbonates. Examples of other solvents include γ-butyrolactone (GBL), α-methyl-γ-butyrolactone (MBL), phosphates (e.g., trimethyl phosphate (PO(OCH3)3), triethyl phosphate (PO(OC2H5)3), tripropyl phosphate (PO(OC3H7)3), tributyl phosphate (PO(OC4H9)3), etc. In particular, if γ-butyrolactone or trimethyl phosphate is used, the increase in ion conduction resistance in a low temperature environment is suppressed, and the discharge performance at low temperatures (below -30°C) can be improved.

[0095] The composite electrolyte may be a gel electrolyte. The gel electrolyte may be formed by compounding an organic electrolyte solution containing lithium ions with a polymer. The gel electrolyte may cover at least a portion of the surface of the inorganic solid particles.

[0096] The gel-like composite electrolyte is obtained, for example, by mixing an electrolyte composition including an organic electrolyte solution containing lithium ions and a polymer with second inorganic solid particles and / or polymer fibers as necessary, and subjecting the mixture to heat treatment as necessary.

[0097] Whether the composite electrolyte is a gel can be confirmed as follows. The gel state can be confirmed by applying 10 g / cm 2 The pressure can be checked by checking whether there is leakage of electrolyte.

[0098] The components that may be contained in the electrolyte described above, such as lithium salt, organic solvent, polymer, polymer fiber, inorganic solid particles, binder, etc., may be one kind or two or more kinds.

[0099] 2) Negative electrode

[0100] The negative electrode includes a negative electrode current collector and a negative electrode active material-containing layer supported on at least one main surface, that is, one surface or both surfaces of the current collector. The negative electrode active material-containing layer includes an active material and may further include a conductive agent and a binder.

[0101] Aluminum foil or aluminum alloy foil can be used as the negative electrode collector. The purity of aluminum foil and aluminum alloy foil can be made to be 98% or more. The upper limit of purity is 100% (pure aluminum). The more preferred aluminum purity is 98% or more and 99.95% or less. If the negative electrode pressing pressure is reduced by using a negative electrode active material containing oxide particles containing titanium, the elongation of the negative electrode collector of the above purity can be reduced. As a result, the electronic conductivity of the negative electrode collector can be improved, and the crushing of the secondary particles containing titanium oxide can be suppressed, so as to produce a low-resistance negative electrode.

[0102] Aluminum alloy is preferably an alloy containing one or more elements selected from iron, magnesium, zinc, manganese and silicon in addition to aluminum. For example, Al-Fe alloys, Al-Mn alloys and Al-Mg alloys can obtain a higher strength than aluminum. On the other hand, it is preferred to make the content of transition metals such as nickel and chromium in aluminum and aluminum alloys less than 100 wtppm (including 0 wtppm). For example, for Al-Cu alloys, the strength is improved, but there is a tendency for the corrosion resistance to decrease.

[0103] The negative electrode active material is not particularly limited as long as it can store and release lithium, and includes carbon materials, graphite materials, lithium alloys, metal oxides, metal sulfides, etc. The type of negative electrode active material used can be one or more. Preferably, the negative electrode active material includes an oxide containing titanium. By using an oxide containing titanium, aluminum foil or aluminum alloy foil can be used for the negative electrode collector instead of copper foil, thereby achieving lightweight and low cost. In addition, it becomes advantageous for the electrode structure of the bipolar structure. The oxide containing titanium preferably has a lithium ion storage and release potential based on the Li potential, and is in the range of 1 to 3 V (vs. Li / Li + ). Examples of titanium-containing oxides that satisfy this condition include lithium titanium oxide, titanium oxide, niobium titanium oxide, sodium niobium titanium oxide, etc. The titanium-containing oxide preferably includes at least one selected from spinel-structured lithium titanium oxide, monoclinic titanium oxide, and niobium titanium oxide.

[0104] Examples of lithium titanium oxides include spinel structure lithium titanium oxides (e.g., general formula Li 4+x Ti5O 12 (x is -1≤x≤3)), ramsdellite-structured lithium titanium oxides (e.g. Li 2+xTi3O7(-1≤x≤3))、Li 1+x Ti2O4(0≤x≤1), Li 1.1+x Ti 1.8 O4(0≤x≤1), Li 1.07+x Ti 1.86 O4(0≤x≤1), etc.

[0105] Examples of titanium oxides include titanium oxides with a monoclinic structure (for example, TiO2(B), Li x TiO2 (x is 0≤x)), rutile titanium oxide (for example, the structure before charging is TiO2, Li x TiO2 (x is 0≤x)), anatase titanium oxide (for example, TiO2, Li x TiO2 (x is 0≤x)).

[0106] Examples of niobium titanium oxides include Li a TiM b Nb 2±β O 7±σ Niobium titanium oxide represented by (0≤a≤5, 0≤b≤0.3, 0≤β≤0.3, 0≤σ≤0.3, M is at least one element selected from Fe, V, Mo and Ta).

[0107] Examples of sodium niobium titanium oxides include those having the general formula Li 2+v Na 2-w M1 x Ti 6-y-z Nb y M2 z O 14+δ An orthorhombic (rectangular) type niobium-titanium composite oxide containing Na represented by (0≤v≤4, 0<w<2, 0≤x<2, 0<y≤6, 0≤z<3, -0.5≤δ≤0.5, 0<6-yz<6, M1 contains at least one selected from Cs, K, Sr, Ba, Ca, and M2 contains at least one selected from Zr, Sn, V, Ta, Mo, W, Fe, Co, Mn, and Al).

[0108] The preferred negative electrode active material is a spinel structure lithium titanium oxide. The volume change of the spinel structure lithium titanium oxide during charge and discharge is small. In addition, since aluminum foil or aluminum alloy foil can be used for the negative electrode collector instead of copper foil, it is possible to achieve lightweight and low cost. Furthermore, it becomes advantageous for the electrode structure of the bipolar structure. It is preferred that the proportion of other negative electrode active materials other than the titanium oxide relative to the entire negative electrode active material is less than 50 weight %.

[0109] The particles containing titanium oxide may include primary particles alone, secondary particles that are aggregates of primary particles, or both primary particles alone and secondary particles.

[0110] The average particle size (diameter) of the secondary particles can be made to be 2 μm or more, preferably larger than 5 μm. More preferably, it is 7 to 20 μm. If it is within this range, a high-density negative electrode can be produced while keeping the pressure of the negative electrode pressing low, and the elongation of the collector containing aluminum can be suppressed. The secondary particles containing titanium oxide are, for example, synthesized by reacting the active material raw material to produce an active material precursor with an average particle size of less than 1 μm, and then calcined. After pulverizing using a pulverizer such as a ball mill or a jet mill, the active material precursor is agglomerated during the calcination process to grow into secondary particles with a large particle size.

[0111] It is preferred that the average particle size (diameter) of the primary particles be 1 μm or less. Thus, the effect becomes significant in high input performance (rapid charging). This is because, for example, the diffusion distance of lithium ions inside the active material becomes shorter and the specific surface area becomes larger. Furthermore, a more preferred average particle size is 0.1 to 0.8 μm. In the negative electrode active material containing layer, secondary particles containing titanium oxide and primary particles may be mixed together. From the viewpoint of further high density, it is preferred that 5 to 50 volume % of primary particles are present in the negative electrode active material containing layer.

[0112] Preferably, at least a portion of the surface of the particles containing titanium oxide is covered with a carbon material layer. This can reduce the negative electrode resistance. By adding a precursor of a carbon material during the secondary particle manufacturing process and calcining at 500° C. or above in an inert atmosphere, at least a portion of the surface of the particles containing titanium oxide can be covered with a carbon material layer.

[0113] The particles containing titanium oxide preferably have an average primary particle size of 1 μm or less and a specific surface area of ​​3 to 200 m2 as measured by a BET method based on N2 adsorption. 2 This can further improve the affinity of the negative electrode with the electrolyte.

[0114] It is preferred that the specific surface area of ​​the negative electrode be 3 to 50 m 2 / g, and a more preferred range is 5 to 50 m 2 / g, and a further preferred range is 1 to 20 m 2 / g. If it is within this range, the reduction decomposition of the electrolyte in a high temperature environment is suppressed, and the cycle life is improved. Here, the so-called specific surface area of ​​the negative electrode means the surface area per 1g of the negative electrode active material containing layer (excluding the weight of the collector). It should be noted that the so-called negative electrode active material containing layer can be a porous layer containing a negative electrode active material, a conductive agent and a binder.

[0115] The porosity of the negative electrode (excluding the current collector) is preferably in the range of 20 to 50%. This allows the negative electrode to have excellent affinity with the electrolyte and a high density. The more preferred range of the porosity is 25 to 40%.

[0116] As the conductive agent, for example, carbon materials, metal compound powders, metal powders, etc. can be used. As carbon materials, for example, acetylene black, carbon black, coke, carbon fiber, graphite, carbon nanotubes, etc. can be listed. The BET specific surface area of ​​the carbon material obtained by N2 adsorption is preferably 10m 2 / g or more. Examples of metal compound powders include powders of TiO, TiC, and TiN. Examples of metal powders include powders of Al, Ni, Cu, and Fe. Examples of preferred conductive agents include coke with an average particle size of less than 10 μm and a heat treatment temperature of 800°C to 2000°C, graphite, acetylene black, carbon fiber with an average fiber diameter of less than 1 μm, and TiO powder. If one or more selected from these is used, a reduction in electrode resistance and an improvement in cycle life performance are achieved. The number of types of conductive agents can be one or more.

[0117] Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, acrylic rubber, styrene butadiene rubber, core-shell adhesives, polyimide, carboxymethyl cellulose (CMC), etc. The binder may be one or more types.

[0118] The types of components that may be contained in the negative electrode described above, such as the negative electrode active material, the conductive agent, the binder, etc., may be one or two or more.

[0119] The mixing ratio of the negative electrode active material, the conductive agent and the binder is preferably in the range of 80 to 95 wt % of the negative electrode active material, 3 to 18 wt % of the conductive agent and 2 to 7 wt % of the binder.

[0120] The negative electrode is produced, for example, by suspending particles of a negative electrode active material, a conductive agent, and a binder in an appropriate solvent, applying the suspension to a current collector, drying the suspension, and performing pressing (for example, heat pressing).

[0121] The average primary particle size of the negative electrode active material is measured by the following method. Using a laser diffraction distribution measuring device (Shimadzu SALD-300 or a device with equivalent functions), first, add about 0.1 g of the sample and a surfactant and 1 to 2 mL of distilled water to a beaker, stir thoroughly, inject into a stirring water tank, measure the photometric distribution 64 times at 2 second intervals, analyze the particle size distribution data, and measure using this method.

[0122] 3) Electrolyte containing layer

[0123] An electrolyte containing layer may be arranged between the positive electrode and the negative electrode. The electrolyte containing layer electrically insulates the positive electrode from the negative electrode and has ion conductivity. Examples of the electrolyte containing layer include a composite electrolyte layer and a separator that retains a liquid or gel electrolyte. Both a composite electrolyte layer and a separator may be used in the electrolyte containing layer.

[0124] When a liquid electrolyte and / or a gel electrolyte is used, a separator may be disposed between the positive electrode and the negative electrode. Examples of the separator include synthetic resin nonwoven fabrics, polyethylene porous films, polypropylene porous films, and cellulose nonwoven fabrics.

[0125] 4) External components

[0126] Examples of the outer packaging member include a laminated film container, a metal container, etc. The shape of the container can be determined according to the form of the secondary battery.

[0127] The thickness of the laminated film is preferably in the range of 0.5 mm or less, and more preferably in the range of 0.2 mm or less. In addition, the lower limit of the thickness of the laminated film is preferably 0.01 mm.

[0128] On the other hand, the preferred range of the plate thickness of the metal container is 0.5 mm or less, and the more preferred range is 0.3 mm or less. In addition, it is preferred that the lower limit of the plate thickness of the metal container is 0.05 mm.

[0129] As a laminated film, for example, a multilayer film including a metal layer and a resin layer covering the metal layer can be cited. In order to reduce weight, the metal layer is preferably an aluminum foil or an aluminum alloy foil. The purity of the aluminum foil is preferably 99.5% by weight or more. The resin layer is used to reinforce the metal layer and can be formed by a polymer such as polypropylene (PP), polyethylene (PE), nylon, polyethylene terephthalate (PET), etc.

[0130] The laminated film container is obtained by laminating laminated films by thermal fusion, for example.

[0131] As a metal container, a square or cylindrical metal can made of aluminum, aluminum alloy, iron, stainless steel, etc. can be used. The metal container is preferably formed of aluminum or an aluminum alloy. As an aluminum alloy, an alloy containing at least one element selected from manganese, magnesium, zinc and silicon is preferred. The aluminum purity of the alloy is preferably 99.8% by weight or less. Since the strength of the metal can made of aluminum alloy increases dramatically, the wall thickness of the can can be thinned. As a result, a thin, lightweight, high-output, and excellent heat dissipation battery can be achieved.

[0132] Metal containers can be sealed using lasers, so the volume of the sealed portion can be reduced and the energy density can be increased compared to laminated film containers.

[0133] The secondary battery of the embodiment can be applied to secondary batteries of various forms such as square, cylindrical, flat, thin, coin-shaped, etc. A secondary battery with a bipolar structure is more preferred. This has the advantage of being able to use one battery to make a secondary battery with the same voltage as a plurality of batteries connected in series. A bipolar battery containing a composite electrolyte can prevent short circuits caused by the electrolyte.

[0134] Reference Figure 1 to Figure 5 An example of the secondary battery according to the embodiment will be described.

[0135] exist Figure 1 and Figure 2 An example of a secondary battery using a metal container is shown in FIG.

[0136] The electrode group 1 is housed in a rectangular cylindrical metal container 2. The electrode group 1 has a structure in which an electrolyte containing layer 5 is interposed between a positive electrode active material containing layer of a positive electrode 3 and a negative electrode active material containing layer of a negative electrode 4, and they are wound in a spiral shape so as to form a flat shape. The electrolyte containing layer 5 covers the surface of the positive electrode active material containing layer or the negative electrode active material containing layer. Figure 2 As shown in , a strip-shaped positive lead 6 is electrically connected to multiple locations of the end of the positive electrode 3 located on the end surface of the electrode group 1. In addition, a strip-shaped negative lead 7 is electrically connected to multiple locations of the end of the negative electrode 4 located on the end surface. The plurality of positive leads 6 are electrically connected to the positive conductive collector sheet 8 in a state of being bundled into one. The positive terminal is composed of the positive lead 6 and the positive conductive collector sheet 8. In addition, the negative lead 7 is connected to the negative conductive collector sheet 9 in a state of being bundled into one. The negative terminal is composed of the negative lead 7 and the negative conductive collector sheet 9. A metal sealing plate 10 is fixed to the opening of the metal container 2 by welding or the like. The positive conductive collector sheet 8 and the negative conductive collector sheet 9 are respectively led out to the outside from the extraction holes provided in the sealing plate 10. In order to avoid short circuits caused by contact with the positive electrode conductive collector tab 8 and the negative electrode conductive collector tab 9 , the inner peripheral surface of each extraction hole of the sealing plate 10 is covered with an insulating member 11 .

[0137] exist Figure 3 and Figure 4 An example of a secondary battery using a laminated film exterior member is shown in FIG.

[0138] like Figure 3 and Figure 4As shown in the figure, the flat wound electrode group 1 is housed in a bag-shaped outer member 12 composed of a laminated film in which a metal layer is interposed between two resin films. The flat wound electrode group 1 is formed by winding a laminated product in which a negative electrode 4, an electrolyte containing layer 15, a positive electrode 3, and an electrolyte containing layer 15 are laminated in this order from the outside into a spiral shape, and then pressing the laminated product. The outermost negative electrode 4 has a Figure 4 As shown in the figure, a negative electrode layer (negative electrode active material containing layer) 4b containing a negative electrode active material is formed on one side of the inner side of the negative electrode collector 4a, and the other negative electrode 4 is formed with negative electrode layers 4b formed on both sides of the negative electrode collector 4a. The positive electrode 3 is formed with positive electrode active material containing layers (positive electrode active material containing layers) 3b formed on both sides of the positive electrode collector 3a.

[0139] Near the outer peripheral end of the wound electrode group 1, the negative terminal 13 is connected to the negative electrode collector 4a of the outermost negative electrode 4, and the positive terminal 14 is connected to the positive electrode collector 3a of the inner positive electrode 3. These negative terminal 13 and positive terminal 14 extend to the outside from the opening of the bag-like outer packaging member 12. The wound electrode group 1 is sealed by heat-sealing the opening of the bag-like outer packaging member 12. When heat-sealing, the negative terminal 13 and the positive terminal 14 are clamped by the bag-like outer packaging member 12 at the opening.

[0140] In each of the examples of the electrolyte-containing layer 5 and the electrolyte-containing layer 15 , a composite electrolyte layer and a separator holding a liquid or gel electrolyte are included. Both the composite electrolyte layer and the separator may be used in the electrolyte-containing layer 5 , 15 .

[0141] Next, a secondary battery having a bipolar structure is described. The secondary battery also includes a current collector having a first face and a second face located on the opposite side of the first face. In the current collector, a current collector similar to the positive electrode current collector or the negative electrode current collector of the secondary battery can be used. The secondary battery has a bipolar structure in which a positive electrode active material containing layer is formed on the first face of the current collector, and a negative electrode active material containing layer is formed on the second face. The composite electrolyte layer is present on the surface of at least one of the positive electrode active material containing layer and the negative electrode active material containing layer. As a result, at least a portion of the composite electrolyte layer is located between the positive electrode active material containing layer and the negative electrode active material containing layer. The positive electrode active material containing layer and the negative electrode active material containing layer can use the same positive electrode active material containing layer and the negative electrode active material containing layer as the positive electrode active material containing layer and the negative electrode active material containing layer described in the secondary battery.

[0142] The composite electrolyte improves the ion conductivity in a secondary battery having a bipolar structure. As a result, a high-voltage secondary battery can be realized with a single unit cell without connecting multiple unit cells in series. Furthermore, since the composite electrolyte can be in a gel-like form, it can prevent short circuits generated through the electrolyte in the bipolar battery.

[0143] An example of a bipolar secondary battery is shown in Figure 5 middle. Figure 5 The secondary battery shown in the figure includes a metal container 31, an electrode body 32 of a bipolar structure, a sealing plate 33, a positive electrode terminal 34 and a negative electrode terminal 35. The metal container 31 has a square tube shape with a bottom. The metal container can use the same metal container as the metal container described in the secondary battery. The electrode body 32 of the bipolar structure includes: a collector 36, a positive electrode layer (positive electrode active material containing layer) 37 stacked on one side (first side) of the collector 36, and a negative electrode layer (negative electrode active material containing layer) 38 stacked on the other side (second side) of the collector 36. The composite electrolyte layer 39 is arranged between the bipolar structure electrode bodies 32. The positive terminal 34 and the negative terminal 35 are fixed to the sealing plate 33 via an insulating member 42, respectively. One end of the positive lead 40 is electrically connected to the positive terminal 34, and the other end is electrically connected to the collector 36. In addition, one end of the negative electrode lead 41 is electrically connected to the negative electrode terminal 35 , and the other end thereof is electrically connected to the current collector 36 .

[0144] Since the secondary battery of the second embodiment described above includes the positive electrode of the first embodiment, it is possible to achieve excellent charge and discharge cycle life, discharge rate performance, and low-temperature performance.

[0145] (Third Embodiment)

[0146] The battery module of the third embodiment includes a plurality of secondary batteries of the second embodiment.

[0147] Examples of battery modules include a battery module including a plurality of cells electrically connected in series and / or in parallel as constituent units, a battery module including a first unit including a plurality of cells electrically connected in series, or a second unit including a plurality of cells electrically connected in parallel, etc. The battery module may include at least one of these constituent units.

[0148] Examples of multiple electrically connected series and / or parallel connections of secondary batteries include examples of electrically connecting multiple batteries each having an outer casing in series and / or in parallel, and examples of electrically connecting multiple electrode groups or bipolar electrode bodies housed in a common casing in series and / or in parallel. A specific example of the former is to connect the positive terminals and negative terminals of multiple secondary batteries with a metal busbar (e.g., aluminum, nickel, copper). A specific example of the latter is to house multiple electrode groups or bipolar electrode bodies in a casing in a state where they are electrochemically insulated by a partition wall, and to connect them electrically in series. In the case of a secondary battery, by making the number of batteries electrically connected in series in the range of 5 to 7, the voltage interchangeability with a lead-acid battery becomes good. In order to further improve the voltage interchangeability with a lead-acid battery, it is preferred to connect 5 or 6 unit cells in series.

[0149] As the case for housing the battery module, a metal can or a plastic container made of aluminum alloy, iron, stainless steel, etc. can be used. In addition, it is preferable that the plate thickness of the container be 0.5 mm or more.

[0150] Reference Figure 6 An example of a battery module will be described. Figure 6 The battery module 21 shown in FIG. 1 has multiple Figure 1 The square secondary batteries 221 to 225 shown in the figure are used as unit batteries. The positive conductive collector sheet 8 of the battery 221 and the negative conductive collector sheet 9 of the battery 222 located at the adjacent position thereof are electrically connected by a lead wire or a bus bar 23. Furthermore, the positive conductive collector sheet 8 of the battery 222 and the negative conductive collector sheet 9 of the battery 223 located at the adjacent position thereof are electrically connected by a lead wire or a bus bar 23. In this way, the batteries 221 to 225 are connected in series.

[0151] Since the battery module of the third embodiment described above includes the secondary battery including the positive electrode of the first embodiment, it is possible to achieve excellent charge and discharge cycle life, discharge rate performance, and low-temperature performance.

[0152] (Fourth Embodiment)

[0153] The battery pack according to the fourth embodiment may include one or more secondary batteries (single batteries) according to the second embodiment. A battery module may be formed by connecting a plurality of secondary batteries in series, in parallel, or in a combination of series and parallel. The battery pack according to the fourth embodiment may include a plurality of battery modules.

[0154] The battery pack according to the fourth embodiment may further include a protection circuit. The protection circuit has a function of controlling the charge and discharge of the secondary battery. Alternatively, a circuit included in a device (such as an electronic device, a car, etc.) that uses the battery pack as a power source may be used as a protection circuit for the battery pack.

[0155] In addition, the battery pack involved in the fourth embodiment can also be further provided with an external terminal for power supply. The external terminal for power supply is used to output the current from the secondary battery to the outside and to input the current into the secondary battery. In other words, when the battery pack is used as a power source, the current is supplied to the outside through the external terminal for power supply. In addition, when the battery pack is charged, the charging current (including the regenerative energy of the power of a vehicle such as a car) is supplied to the battery pack through the external terminal for power supply.

[0156] exist Figure 7 and Figure 8 An example of a battery pack 50 is shown in FIG. The battery pack 50 includes a plurality of Figure 3 A flat battery with the structure shown in FIG. Figure 7 is an exploded perspective view of the battery pack 50, Figure 8 To express Figure 7 A block diagram of the circuit of the battery pack 50 is shown.

[0157] A plurality of single cells 51 are stacked so that the negative electrode terminals 13 and the positive electrode terminals 14 extending outward are aligned in the same direction and bonded with adhesive tape 52 to form a battery module 53. Figure 8 are electrically connected in series as shown in .

[0158] The printed wiring substrate 54 is arranged opposite to the side of the single cell 51 where the negative electrode terminal 13 and the positive electrode terminal 14 extend. Figure 8 As shown in the figure, a thermistor 55, a protective circuit 56 and an external terminal 57 for supplying power to an external device are mounted. In addition, an insulating plate (not shown) is installed on the surface of the printed wiring substrate 54 facing the battery module 53 to avoid unnecessary connection with the wiring of the battery module 53.

[0159] The positive electrode side lead 58 is connected to the positive electrode terminal 14 located at the bottom layer of the battery module 53, and its front end is inserted into the positive electrode side connector 59 of the printed wiring substrate 54 for electrical connection. The negative electrode side lead 60 is connected to the negative electrode terminal 13 located at the top layer of the battery module 53, and its front end is inserted into the negative electrode side connector 61 of the printed wiring substrate 54 for electrical connection. These connectors 59 and 61 are connected to the protection circuit 56 through wiring 62 and 63 formed on the printed wiring substrate 54.

[0160] The thermistor 55 detects the temperature of the single cell 51 and transmits its detection signal to the protection circuit 56. The protection circuit 56 is capable of blocking the positive side wiring 64a and the negative side wiring 64b between the protection circuit 56 and the power supply terminal 57 for the external device as the external terminal for power supply under specified conditions. The so-called specified conditions are, for example, when the detection temperature of the thermistor 55 becomes higher than the specified temperature. In addition, the so-called specified conditions are when overcharge, overdischarge, overcurrent, etc. of the single cell 51 are detected. The overcharge and other detections are performed on each single cell 51 or on all the single cells 51. When detecting each single cell 51, the battery voltage can be detected, and the positive electrode potential or the negative electrode potential can also be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each single cell 51. Figure 7 and Figure 8 In this case, wirings 65 for voltage detection are connected to the individual cells 51 , and detection signals are transmitted to the protection circuit 56 via these wirings 65 .

[0161] Protective sheets 66 made of rubber or resin are disposed on three side surfaces of the battery module 53 except for the side surfaces from which the positive electrode terminal 14 and the negative electrode terminal 13 protrude.

[0162] The battery module 53 is housed in the housing container 67 together with the protective sheets 66 and the printed wiring substrate 54. That is, the protective sheets 66 are respectively arranged on the two inner side surfaces in the long side direction and the inner side surface in the short side direction of the housing container 67, and the printed wiring substrate 54 is arranged on the inner side surface on the opposite side in the short side direction. The battery module 53 is located in the space surrounded by the protective sheets 66 and the printed wiring substrate 54. The cover 68 is mounted on the upper surface of the housing container 67.

[0163] Furthermore, a heat shrink tape may be used to fix the battery module 53 instead of the adhesive tape 52. In this case, protective sheets are placed on both sides of the battery module, and after the heat shrink tape is wound, the heat shrink tape is thermally shrunk to bundle the battery modules.

[0164] Figure 7 , Figure 8 , single cells 51 are connected in series, but they can also be connected in parallel to increase the battery capacity. Alternatively, the series connection and the parallel connection can be combined. The assembled battery pack can also be further connected in series or in parallel.

[0165] In addition, Figure 7 and Figure 8 The battery pack shown in FIG. 1 includes one battery module, but the battery pack according to the third embodiment may include a plurality of battery modules. The plurality of battery modules are electrically connected in series, in parallel, or in a combination of series and parallel connections.

[0166] In addition, the form of the battery pack is appropriately changed according to the purpose. The battery pack involved in this embodiment is suitable for use in applications that require excellent cycle performance when a large current is taken out. Specifically, it is used as a power source for a digital camera, or, for example, as a vehicle battery such as a two-wheeled or even four-wheeled hybrid electric vehicle, a two-wheeled or even four-wheeled electric vehicle, a power-assisted bicycle or a railway vehicle (such as a tram), or a fixed battery. In particular, it is suitable for use as a vehicle-mounted battery mounted on a vehicle.

[0167] Since the battery pack of the fourth embodiment described above includes the secondary battery including the positive electrode of the first embodiment, it is possible to achieve excellent charge and discharge cycle life, discharge rate performance, and low-temperature performance.

[0168] (Fifth Embodiment)

[0169] The vehicle of the fifth embodiment includes one or two or more secondary batteries of the second embodiment, or includes the battery module of the third embodiment or the battery pack of the fourth embodiment.

[0170] In a vehicle such as a car equipped with a battery pack according to the fifth embodiment, the battery pack can recover regenerative energy of the vehicle's power, for example. In addition, the vehicle can include a mechanism that converts the vehicle's kinetic energy into regenerative energy.

[0171] exist Fig. 9 Detailed Description of the Invention An example of a vehicle including a battery pack according to an example of the fourth embodiment is shown.

[0172] Fig. 9 The car 71 shown in FIG. 1 has a battery pack 72 according to an example of the fourth embodiment mounted in the engine room in front of the car body. The mounting position of the battery pack in the car is not limited to the engine room. For example, the battery pack can also be mounted behind the car body or under the seat. Fig.10 It is a diagram schematically showing the structure of an example of a vehicle according to the embodiment. Fig.10 The vehicle 300 shown in FIG. 1 is an electric vehicle.

[0173] Fig.10 The vehicle 300 shown in FIG. 1 includes a vehicle power supply 301 , a vehicle ECU (ECU: Electrical Control Unit) 380 as a higher-level control means for the vehicle power supply 301 , an external terminal 370 , an inverter 340 , and a drive motor 345 .

[0174] The vehicle 300 has a vehicle power supply 301 mounted in, for example, the engine room, the rear of the vehicle body, or under a seat. Fig.10 , the mounting location of the secondary battery in the vehicle 300 is schematically shown.

[0175] The vehicle power supply 301 includes a plurality of (eg, three) battery packs 312 a , 312 b , and 312 c , a battery management unit (BMU: Battery Management Unit) 311 , and a communication bus 310 .

[0176] Three battery packs 312a, 312b, and 312c are electrically connected in series. Battery pack 312a includes a battery module 314a and a battery module monitoring device (VTM: Voltage Temperature Monitoring) 313a. Battery pack 312b includes a battery module 314b and a battery module monitoring device 313b. Battery pack 312c includes a battery module 314c and a battery module monitoring device 313c. Battery packs 312a, 312b, and 312c can be removed independently and replaced with other battery packs.

[0177] Each of the battery modules 314a to 314c includes a plurality of secondary batteries connected in series. Each of the secondary batteries is a secondary battery according to the embodiment. Each of the battery modules 314a to 314c is charged and discharged through a positive electrode terminal 316 and a negative electrode terminal 317.

[0178] The battery management device 311 communicates with the battery module monitoring devices 313 a to 313 c to collect information related to the maintenance of the vehicle power supply 301 , and collects information such as the voltage and temperature of the secondary batteries of the battery modules 314 a to 314 c included in the vehicle power supply 301 .

[0179] A communication bus 310 is connected between the battery management device 311 and the battery module monitoring devices 313a to 313c. The communication bus 310 is configured so that a plurality of nodes (nodes of the battery management device and one or more battery module monitoring devices) share a set of communication lines. The communication bus 310 is a communication bus configured based on, for example, the CAN (Controller Area Network) standard.

[0180] The battery module monitoring devices 313a to 313c measure the voltage and temperature of each secondary battery constituting the battery modules 314a to 314c based on the command generated by the communication from the battery management device 311. However, the temperature can be measured at only a few points in one battery module, and the temperature of all the secondary batteries need not be measured.

[0181] The vehicle power supply 301 may also include an electromagnetic contactor (eg, Fig.10The switch device 333 shown in FIG. 3 includes a pre-charge switch (not shown) that is turned on when charging the battery modules 314a to 314c, and a main switch (not shown) that is turned on when supplying the battery output power to the load. The pre-charge switch and the main switch have a relay circuit (not shown) that is turned on or off according to a signal supplied to a coil arranged near the switch element.

[0182] The inverter 340 converts the input DC voltage into a three-phase AC high voltage for motor driving. The inverter 340 controls the output voltage based on a control signal from a battery management device 311 described later or a vehicle ECU 380 for controlling the operation of the entire vehicle. The three-phase output terminals of the inverter 340 are connected to the three-phase input terminals of the drive motor 345.

[0183] The drive motor 345 is rotated by the electric power supplied from the inverter 340 , and the rotation is transmitted to the axle and the drive wheels W via, for example, a differential gear unit.

[0184] Although not shown, the vehicle 300 has a regenerative braking mechanism that rotates the drive motor 345 when braking the vehicle 300, converting kinetic energy into regenerative energy as electrical energy. The regenerative energy recovered by the regenerative braking mechanism is input to the inverter 340 and converted into a direct current. The direct current is input to the vehicle power supply 301.

[0185] One terminal of the connection line L1 is connected to the negative terminal 317 of the vehicle power supply 301 via a current detection unit (not shown) in the battery management device 311. The other terminal of the connection line L1 is connected to the negative input terminal of the inverter 340.

[0186] One terminal of the connection line L2 is connected to the positive terminal 316 of the vehicle power supply 301 via the switching device 333. The other terminal of the connection line L2 is connected to the positive input terminal of the inverter 340.

[0187] The external terminal 370 is connected to a battery management device 311 described later. The external terminal 370 can be connected to an external power source, for example.

[0188] The vehicle ECU 380 controls the battery management device 311 in coordination with other devices in response to the operation input of the driver, etc., and manages the entire vehicle. The battery management device 311 and the vehicle ECU 380 transmit data related to the maintenance of the vehicle power supply 301, such as the remaining capacity of the vehicle power supply 301, via a communication line.

[0189] The vehicle according to the fifth embodiment includes a battery pack including the secondary battery according to the embodiment, and the battery pack (e.g., the battery packs 312a, 312b, and 312c) has excellent charge and discharge cycle life, discharge rate performance, and low temperature performance, so a vehicle with excellent charge and discharge performance and high reliability is obtained. Furthermore, since each battery pack is low in price and high in safety, the cost of the vehicle can be suppressed and the safety can be improved.

[0190] (Sixth Embodiment)

[0191] According to the sixth embodiment, an electrode comprising active material particles, polymer fibers and inorganic solid particles is provided. The average fiber diameter of the polymer fibers is greater than 1 nm and less than 100 nm. That is, the first embodiment is applied to the positive electrode, but can also be applied to the negative electrode. Alternatively, the first embodiment can be applied to both the positive electrode and the negative electrode.

[0192] The electrodes according to the embodiments are described below.

[0193] The reason for limiting the average fiber diameter of the polymer fiber is explained. If the average fiber diameter exceeds 100nm, it becomes difficult to distribute the polymer fiber in detail in the negative electrode or other electrodes. In addition, since the specific surface area of ​​the polymer fiber is insufficient, the amount of electrolyte that can be retained in the polymer fiber becomes less. As a result, the low temperature performance or discharge rate performance of the battery is reduced. It is preferred that the average fiber diameter is small, but if it is less than 1nm, the dispersion of the fibers in the electrode becomes insufficient, and the fibers can no longer evenly retain the electrolyte. The more preferred range of the average fiber diameter is greater than 5nm and less than 50nm.

[0194] The polymer fiber with an average fiber diameter of 1 nm or more and 100 nm or less is easily dispersed in the negative electrode and other electrodes to form a fine mesh space because the fiber diameter is nanometer-sized. As a result, the electrolyte such as liquid electrolyte and gel electrolyte is loaded or maintained on the polymer fiber, so that the ion conduction cutoff associated with the expansion and contraction of the active material particles can be suppressed, and the ion conduction resistance in the electrode can be reduced. Therefore, the secondary battery with the electrode can improve the charge and discharge cycle life, discharge rate performance and low temperature performance.

[0195] The polymer fiber is preferably cellulose fiber (cellulose nanofiber). Cellulose fiber is a nanometer-sized fiber diameter with an average fiber diameter of more than 1nm and less than 100nm, and an aspect ratio (more than 100 and less than 10000) is very large, and a liquid electrolyte can be firmly maintained in the fine mesh space of the fiber. By containing cellulose fiber in the polymer fiber, the aspect ratio of the polymer fiber can be greatly increased, for example, more than 100 and less than 10000, so the formation of the fine mesh space produced by the polymer fiber can be promoted. As a result, the electrolyte is further suppressed from being separated from the electrode, so the ion conduction resistance in the electrode can be further reduced. Therefore, the secondary battery equipped with the electrode can further improve the charge and discharge cycle life, discharge rate performance and low temperature performance.

[0196] By including at least one selected from Al2O3, TiO2, ZrO2 and a phosphoric acid compound in the inorganic solid particles, the inorganic solid particles can conduct lithium ions without being solvated, thereby promoting ion conduction in the electrode.

[0197] The inorganic solid particles are preferably at least one selected from Al2O3, TiO2, ZrO2 and phosphoric acid compounds. In addition, as phosphoric acid compounds, for example, AlPO4, Li3PO4, a NASICON-type structure and composed of Li 1+y Al x M 2-x Phosphoric acid compounds represented by (PO4)3 (M is at least one element selected from Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1) etc. having a NASICON structure and consisting of Li 1+y Al x M 2-x The phosphoric acid compound represented by (PO 4 ) 3 has excellent stability in air and obtains high lithium ion conductivity.

[0198] Preferably, the phosphate compound contains: a NASICON-type structure and a Li 1+y Al x M 2-x A compound represented by (PO4)3 (M is at least one element selected from Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1). It is believed that at the interface of liquid or gel electrolyte, inorganic solid particles and active material particles maintained in a fine mesh space formed by polymer fibers, the lithium ion concentration is increased without being affected by solvation, and high-speed lithium ion conduction is manifested, thereby reducing the ion conduction resistance in the electrode and the resistance at the interface of the active material particles.

[0199] The average particle size of the inorganic solid particles can be less than 1 μm. The more preferred range is 0.01 μm or more and 1 μm or less, and the further preferred range is 0.05 μm or more and 0.6 μm or less. If it is within this range, the lithium ion conductivity in the electrode is improved, so the resistance of the electrode becomes smaller. By compounding the polymer fibers and the inorganic solid particles, high-speed ion conductivity can be maintained even in electrodes with large expansion and contraction. In particular, at the interface between the liquid, gel electrolyte and the inorganic solid particles with an average particle size of less than 1 μm and the active material particles with high potential maintained in the fine mesh space formed by the polymer fibers, it is believed that the lithium ion concentration that is not affected by the solvation increases, and high-speed lithium ion conduction appears, which reduces the ion conduction resistance in the electrode and the resistance of the active material interface.

[0200] It is preferred that the content of the polymer fiber in the active material containing layer is 0.2% by weight or more and 10% by weight or less. If the content of the polymer fiber exceeds 10% by weight, the content of the components other than the polymer fiber becomes relatively less, so sometimes the density of the electrode decreases. In addition, if the content of the polymer fiber is less than 0.2% by weight, the effect of the polymer fiber having an average fiber diameter of 1 nm or more and 100 nm or less cannot be obtained, and sometimes the charge and discharge cycle life, discharge rate performance, and low temperature performance are reduced. The more preferred range of the content is 0.2% by weight or more and 5% by weight or less, and the more preferred range is 0.3% by weight or more and 2% by weight or less.

[0201] Preferably, the content of the inorganic solid particles in the active material containing layer is 0.5% by weight or more and 10% by weight or less. If the content of the inorganic solid particles exceeds 10% by weight, the content of the components other than the inorganic solid particles decreases relatively, so the density of the electrode is reduced sometimes. In addition, if the content of the inorganic solid particles is less than 0.5% by weight, the effect of the inorganic solid particles cannot be obtained, and the charge-discharge cycle life, discharge rate performance and low temperature performance are reduced sometimes. The more preferred range of content is 1% by weight or more and 6% by weight or less.

[0202] By setting the polymer fiber content to 0.2 wt % to 5 wt % and the inorganic solid particle content to 0.5 wt % to 10 wt %, the lithium ion conduction resistance and electron conduction resistance of the electrode can be reduced while maintaining a high electrode density.

[0203] The electrode may include a current collector and an active material containing layer loaded on at least one main surface, i.e., one surface or both surfaces, of the current collector. The active material containing layer includes active material particles, polymer fibers having an average fiber diameter of 1 nm or more and 100 nm or less, and inorganic solid particles. The active material containing layer may further include a conductive agent and a binder.

[0204] The electrode may contain an electrolyte. As a polymer for gelling the electrolyte in the electrode, for example, a polymer gelled with a carbonate can be cited. Examples of such polymers include polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), polymethyl methacrylate, etc. The gel polymer electrolyte using polyacrylonitrile has high ion conductivity, and the discharge performance and low temperature performance are improved, so it is preferred. The proportion of the gel polymer electrolyte in the active material containing layer is preferably 1% by weight or more and 10% by weight or less. If it deviates from this range, the low temperature performance and discharge performance are sometimes reduced.

[0205] Aluminum foil or aluminum alloy foil can be used as the current collector. Examples of the aluminum foil and aluminum alloy foil include the same examples as those described for the negative electrode current collector of the second embodiment.

[0206] The active material particles are not particularly limited as long as they can store and release lithium. Examples of the negative electrode active material include the same examples as those described in the second embodiment.

[0207] The specific surface area of ​​the negative electrode is preferably 3 to 50 m 2 / g, and a more preferred range is 5 to 50 m 2 / g, and a further preferred range is 1 to 20 m 2 / g.

[0208] The porosity of the negative electrode (excluding the current collector) is preferably in the range of 20 to 50% for the same reasons as described in the second embodiment. A more preferred range of the porosity is 25 to 40%.

[0209] Examples of the conductive agent include the same examples as those described in the negative electrode of Embodiment 2. Carbon nanotubes and carbon nanofibers as an example of carbon fibers are easily entangled in the active material particles and can appropriately cover the surfaces of the active material particles.

[0210] Examples of the binder include the same examples as those described in the negative electrode of the second embodiment. The binder can impart flexibility to the active material-containing layer including the polymer fiber. PVdF and styrene butadiene rubber are excellent in the effect of improving flexibility.

[0211] The components that may be contained in the electrode described above, such as active material, polymer fiber, inorganic solid particles, conductive agent, binder, etc., may be one kind or two or more kinds.

[0212] It is preferred that the mixing ratio of the negative electrode active material, conductive agent, binder, polymer fiber, and inorganic solid particles be in the range of 80 to 95 weight % of negative electrode active material, 1 to 8 weight % of conductive agent, 0.5 to 3 weight % of binder, 0.2 to 5 weight % of polymer fiber, and 0.5 to 10 weight % of inorganic solid particles.

[0213] The negative electrode is produced, for example, by dispersing particles of a negative electrode active material, polymer fibers, inorganic solid particles, a conductive agent, and a binder in a solvent, applying the obtained dispersion to a current collector, drying, and pressing (for example, heating and pressing). Alternatively, particles of a negative electrode active material, a conductive agent, and a binder are dispersed in a solvent to obtain a first dispersion. In addition, polymer fibers and inorganic solid particles are dispersed in a solvent to obtain a second dispersion. After applying the first dispersion to the current collector, the second dispersion is applied to the layer of the first dispersion on the current collector. Next, the negative electrode is obtained by drying and pressing (for example, heating and pressing). Application of the dispersion to the current collector is carried out, for example, using a sprayer, a die coater, or the like.

[0214] The following is a method for determining the content of polymer fibers in the active material containing layer. The active material containing layer peeled from the current collector is crushed using a mortar or the like, the crushed material is dispersed in water, and the polymer fibers are separated using the specific gravity difference. The polymer fibers in the supernatant are dried at 100°C for 12 hours, the weight of the polymer fibers is measured, and the content of the polymer fibers in the active material containing layer is determined.

[0215] The polymer fibers whose weight was measured by the above method were observed with a scanning electron microscope (SEM) at a magnification of 10,000 times, and the widths at 25%, 50%, and 75% of the total length of the polymer fibers in the field of view were measured. The average of the measured width values ​​was taken as the average fiber diameter. The measurement was performed on all polymer fibers present in the field of view.

[0216] The following describes a method for determining the content of solid inorganic particles in an active material-containing layer. The active material-containing layer that has been subjected to an electrolyte removal treatment using the method described later is crushed using a mortar or the like, the crushed material obtained is dispersed in water, and the polymer fibers and the conductive agent are separated using a specific gravity difference. The polymer fibers and the conductive agent in the supernatant are removed. The precipitate is washed with dimethyl carbonate to remove the binder. Next, the mixture is dried, and the particle size distribution data of the obtained powder is obtained using the laser diffraction described later. Based on the obtained particle size distribution data, the content of solid inorganic particles in the active material-containing layer is calculated.

[0217] The average primary particle size of active material particles and solid inorganic particles is measured by the following method. Using a laser diffraction distribution measuring device (Shimadzu SALD-300 or a device with equivalent functions), first, add about 0.1 g of sample, surfactant and 1 to 2 mL of distilled water to a beaker, stir thoroughly, pour into a stirring water tank, measure the photometric distribution 64 times at 2 second intervals, analyze the particle size distribution data, and measure using this method.

[0218] When confirming the average fiber diameter of the polymer fiber, etc. for the electrode contained in the secondary battery, the electrode is taken out from the secondary battery by the following method. The secondary battery is decomposed in a glove box filled with argon gas, and the electrode is taken out. The active material containing layer is peeled off from the collector of the taken-out electrode. Next, the active material containing layer is washed with dimethyl carbonate to remove the electrolyte, and then dried. Then, the average fiber diameter of the polymer fiber, etc. is confirmed.

[0219] According to the sixth embodiment, an electrode is provided, which includes active material particles, polymer fibers having an average fiber diameter of 1 nm or more and 100 nm or less, and inorganic solid particles. The electrode of the sixth embodiment can suppress the increase in ion conduction resistance caused by the expansion and contraction of the active material particles. Therefore, a secondary battery having the electrode can improve charge and discharge cycle life, discharge rate performance, and low temperature performance.

[0220] The secondary battery of the second embodiment can use the electrode of the sixth embodiment as the negative electrode instead of the negative electrode without polymer fibers and inorganic solid particles. In this case, the positive electrode without polymer fibers or inorganic solid particles can be used as the positive electrode of the secondary battery. The positive electrode without polymer fibers or inorganic solid particles has the same structure as the positive electrode of the first embodiment except that it does not contain polymer fibers or inorganic solid particles.

[0221] A secondary battery using the electrode of the sixth embodiment for at least one of the positive electrode and the negative electrode can improve the charge and discharge cycle life, discharge rate performance and low temperature performance. The secondary battery can be applied to the battery module of the third embodiment, the battery pack of the fourth embodiment or the vehicle of the fifth embodiment. Thus, a battery module and a battery pack having excellent charge and discharge cycle life, discharge rate performance and low temperature performance can be realized, and in addition, a vehicle with excellent charge and discharge performance and high reliability can be provided.

[0222] The electrode of the sixth embodiment may contain a gel-like electrolyte. The electrode containing a gel-like electrolyte is obtained, for example, by impregnating at least one of the positive electrode and the negative electrode produced by the above method with an electrolyte composition containing a liquid electrolyte and a polymer, and then subjecting it to heat treatment as needed. The gelation treatment can be applied to the electrode monomer or to the electrode group. The polymer is not particularly limited as long as it can gel the liquid electrolyte containing lithium ions, and both chemical gelling agents and physical gelling agents can be used. For example, polyacrylonitrile (PAN), polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), polymethyl methacrylate and other polymers that are gelled with carbonates can be listed. The type of polymer can be one or more than two.

[0223] Example

[0224] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings, but the present invention is not limited to the embodiments disclosed below.

[0225] (Example 1)

[0226] As positive electrode active material particles, LiNi with an average secondary particle size of 5 μm was prepared. 0.8 Co 0.1 Mn 0.1 O2 secondary particles. Lithium ions with an average primary particle size of 0.4 μm were mixed into 89.5 wt% of the positive electrode active material particles. 1.3 Al 0.3 Zr 1.7 2 wt% of (PO4)3 particles, 0.5 wt% of cellulose nanofibers with an average fiber diameter of 10 nm, 5 wt% of graphite powder as a conductive agent, and 3 wt% of PVdF as a binder were dispersed in N-methylpyrrolidone (NMP) solvent to prepare a slurry, which was then coated on both sides of a 15 μm thick aluminum alloy foil (purity 99%), dried, and pressed to produce an electrode with a density of 3.1 g / cm 3 The positive electrode.

[0227] As negative electrode active material particles, particles with an average primary particle size of 0.6 μm and a specific surface area of ​​10 m 2 / gLi4Ti5O 12 Particles. The negative electrode active material particles, graphite powder with an average particle size of 6 μm as a conductive agent, and PVdF as a binder are mixed in a weight ratio of 95:3:2, dispersed in N-methylpyrrolidone (NMP) solvent, and stirred using a ball mill at a speed of 1000 rpm and a stirring time of 2 hours to prepare a slurry. The obtained slurry is applied to an aluminum alloy foil (purity 99.3%) with a thickness of 15 μm, dried, and subjected to a heating and pressing process to produce an electrode density of 2.2 g / cm2 on a single-sided negative electrode layer.3 The negative electrode excluding the current collector has a porosity of 35%.

[0228] As the electrolyte-containing layer, a composite electrolyte layer was prepared. Li 1.3 Al 0.3 Zr 1.7 An aqueous solution of 5 wt% (PO4)3 particles and 0.5 wt% cellulose nanofibers with an average fiber diameter of 10 nm was applied to the two main surfaces of the positive electrode active material containing layer and the two main surfaces of the negative electrode active material containing layer, and then dried to obtain an electrolyte containing layer precursor. The positive electrode and the negative electrode were stacked so that the electrolyte containing layer precursor was located between the positive electrode active material containing layer and the negative electrode active material containing layer, and wound into a flat spiral shape to obtain an electrode group. The electrode group was housed in a thin metal can made of aluminum alloy (Al purity 99%) with a thickness of 0.25 mm.

[0229] A liquid non-aqueous electrolyte was obtained by dissolving 1M LiPF6 in a solvent in which propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a volume ratio of PC:DEC of 1:2. 80 wt% of the liquid non-aqueous electrolyte was mixed with 20 wt% of a polymer composed of polyacrylonitrile (PAN). The resulting mixed solution was injected into a metal can and allowed to penetrate into the gap between the positive electrode and the negative electrode. Then, a gel-like composite electrolyte layer with a thickness of 5 μm was formed by heat treatment at 60°C for 24 hours. In the composite electrolyte layer, Li 1.3 Al 0.3 Zr 1.7 The weight ratio of (PO4)3 particles, a gel polymer composed of a non-aqueous electrolyte and a polymer solution of polyacrylonitrile (PAN), and cellulose nanofibers is 94:4:2.

[0230] After the above steps, the above-mentioned Figure 1 The structure shown is a square non-aqueous electrolyte secondary battery with a thickness of 13 mm, a width of 62 mm, and a height of 96 mm.

[0231] (Examples 2 to 22 and Comparative Examples 1 to 8)

[0232] A secondary battery is manufactured in the same manner as described in Example 1, except that the composition and content of the positive electrode active material, negative electrode active material, and inorganic solid particles, and the average fiber diameter and content of the polymer fibers are as shown in the following Tables 1 and 2, the composition of the positive electrode active material containing layer is as shown in Tables 3 and 4, and the average secondary particle size of the positive electrode active material in Example 12 is 10 μm, the average secondary particle size of the positive electrode active material in Example 13 is 5 μm, the average secondary particle size of the negative electrode active materials in Examples 14 to 19 is 8 μm, and the average primary particle size is 0.6 μm.

[0233] (Example 23)

[0234] An electrode group was prepared in the same manner as described in Example 1, and the electrode group was housed in a thin metal can similar to the metal can described in Example 1.

[0235] A liquid nonaqueous electrolyte having the same composition as that described in Example 1 was injected into the metal can and allowed to penetrate into the gap between the positive electrode and the negative electrode. Then, the metal can was sealed to obtain a Figure 1 A square nonaqueous electrolyte secondary battery having the structure shown in and the same dimensions as those described in Example 1.

[0236] (Example 24)

[0237] A separator made of a cellulose fiber nonwoven fabric having a thickness of 20 μm was used instead of the electrolyte containing layer precursor. The positive electrode and the negative electrode were stacked so that the separator was located between the positive electrode active material containing layer and the negative electrode active material containing layer, and wound into a flat spiral shape to produce an electrode group, which was housed in a thin metal can similar to the metal can described in Example 1.

[0238] A liquid nonaqueous electrolyte having the same composition as that described in Example 1 was injected into the metal can and allowed to penetrate into the gap between the positive electrode and the negative electrode. Then, the metal can was sealed to obtain a Figure 1 A square nonaqueous electrolyte secondary battery having the structure shown in and the same dimensions as those described in Example 1.

[0239] The obtained secondary batteries of the examples and comparative examples were charged to 2.9 V at a constant current of 12 A at 25° C., and then charged at a constant voltage of 2.9 V. The charging was terminated when the current value reached 0.05 A. Next, the discharge capacity when discharged to 1.5 V at 6 A was measured as the discharge capacity at 25° C. The results are shown in Tables 5 and 6.

[0240] As the charge and discharge cycle performance, after charging to 2.9V at a constant current of 12A at 25°C, constant voltage charging was performed at 2.9V, and charging was terminated when the current value reached 0.05A. Next, it was discharged to 1.5V at 6A. The capacity retention rate after repeating the charge and discharge cycle 5000 times was measured. The discharge capacity of the first cycle was set to 100%, and the value representing the discharge capacity of the 5000th cycle was taken as the capacity retention rate at 5000 times, which is shown in Tables 5 and 6.

[0241] As the high current discharge performance, the battery was charged to 2.9V at a constant current of 12A at 25°C, then charged at a constant voltage of 2.9V, and the charging was terminated when the current value reached 0.05A. Next, the capacity retention rate during 5C (30A) discharge was measured. The capacity retention rate was calculated by setting the capacity during 0.2C (1.2A) discharge to 100%.

[0242] As the low-temperature discharge performance, the battery was charged to 2.9 V at a constant current of 12 A at 25°C, then charged at a constant voltage of 2.9 V, and the charging was terminated when the current value reached 0.05 A. Next, the capacity retention rate at 1.2 A discharge at -30°C was measured. The capacity retention rate was calculated by setting the discharge capacity at 25°C as 100%.

[0243] These measurement results are shown in Tables 5 and 6 below.

[0244]

Table 1

[0245]

[0246]

Table 2

[0247]

[0248]

Table 3

[0249]

[0250]

Table 4

[0251]

[0252]

Table 5

[0253]

[0254]

Table 6

[0255]

[0256] As shown in Table 2, the balance of cycle life performance, discharge rate performance, and low-temperature discharge performance of Examples 1 to 15 of the secondary battery is excellent compared with Comparative Examples 1 to 8. By comparing Example 1 with Example 23, it can be seen that Example 23, which includes a liquid electrolyte instead of a gel electrolyte, obtains the same cycle life performance, discharge rate performance, and low-temperature discharge performance as Example 1. In addition, by comparing Example 1 with Example 24, it can be seen that Example 1 including a composite electrolyte layer has excellent cycle life performance, discharge rate performance, and low-temperature discharge performance compared with Example 24 including a separator instead of a composite electrolyte layer.

[0257] According to the positive electrode of at least one of these embodiments or examples, since it contains polymer fibers and inorganic solid particles having an average fiber diameter of 1 nm or more and 100 nm or less, it is possible to reduce the ion conduction resistance in the positive electrode. Therefore, a secondary battery having the positive electrode can improve charge and discharge cycle life, discharge rate performance, and low temperature performance.

[0258] (Example 30)

[0259] LiNi with an average secondary particle size of 5 μm as the positive electrode active material 0.8 Co 0.1 Mn 0.1 92 wt% of O2 secondary particles, 5 wt% of graphite powder as a conductive agent, and 3 wt% of PVdF as a binder were dispersed in N-methylpyrrolidone (NMP) solvent to prepare a slurry. The obtained slurry was coated on both sides of a 15 μm thick aluminum alloy foil (purity 99%), dried, and pressed to produce an electrode with a density of 3.1 g / cm 3 The positive electrode.

[0260] The average secondary particle size of the negative electrode active material is 10 μm and the specific surface area is 5 m 2 / g TiNb2O7 secondary particles 88 wt%, average primary particle size 0.4 μm Li 1.3 Al 0.3 Zr 1.7 3 wt% of (PO4)3 particles, 5 wt% of graphite powder with an average particle size of 6 μm as a conductive agent, 2 wt% of cellulose nanofibers with an average fiber diameter of 50 nm, and 2 wt% of carboxymethyl cellulose (CMC) as a binder were dispersed in water and stirred in a ball mill at a speed of 1000 rpm and a stirring time of 2 hours to prepare a slurry. The obtained slurry was applied to both sides of an aluminum alloy foil (purity 99.3%) with a thickness of 15 μm, dried, and subjected to a heating and pressing process to produce a negative electrode active material containing layer with a density of 2.7 g / cm 3 The negative electrode excluding the current collector has a porosity of 40%.

[0261] As the electrolyte, a composite electrolyte was used. Li 1.3 Al 0.3 Zr 1.7 An aqueous solution of (PO4)3 particles and cellulose nanofibers having an average fiber diameter of 10 nm was applied to the surfaces (main surfaces) of both the positive electrode active material-containing layer and the negative electrode active material-containing layer and dried to form an electrolyte precursor layer.

[0262] The positive electrode and the negative electrode are overlapped so that the electrolyte precursor layer is located between them to make an electrode group. The electrode group is placed in a thin metal can container made of aluminum alloy (Al purity 99%) with a plate thickness of 0.25 mm. Next, a 2% by weight solution of a liquid non-aqueous electrolyte and a polymer of polyacrylonitrile, which is prepared by dissolving 1M LiPF6 in a non-aqueous solvent mixed with propylene carbonate (PC) and diethyl carbonate (DEC) in a volume ratio of 1:2, is injected into the metal can container so that it penetrates into the gap between the positive electrode and the negative electrode. Then, the electrolyte precursor layer is gelled by heating to 60°C, and a gel electrolyte layer with a thickness of 15 μm is formed between the positive electrode and the negative electrode. As for the composition of the obtained gel electrolyte layer, the weight ratio of inorganic solid particles, gel electrolyte composed of a polymer of non-aqueous electrolyte and polyacrylonitrile, and cellulose nanofibers is 94:4:2.

[0263] After the above steps, the above-mentioned Figure 1 The structure shown is a square non-aqueous electrolyte secondary battery with a thickness of 13 mm, a width of 62 mm, and a height of 96 mm.

[0264] (Examples 31 to 40 and Comparative Examples 11 to 16)

[0265] A secondary battery is prepared in the same manner as described in Example 30, except that the composition of the positive electrode active material, the composition of the negative electrode active material, the composition of the inorganic solid particles, the content of inorganic solid particles in the negative electrode active material containing layer, the average fiber diameter of the polymer fibers, the content of the polymer fibers in the negative electrode active material containing layer, and the contents of the negative electrode active material, the conductive agent, and the binder in the negative electrode active material containing layer are as shown in the following Tables 7 to 9.

[0266] It should be noted that the average secondary particle size of the monoclinic titanium dioxide (TiO2(B)) as the negative electrode active material in Example 39 was 15 μm, and the specific surface area was 20 m 2 / g. In addition, the negative electrode active material of Example 40 used an average primary particle size of 0.6 μm and a specific surface area of ​​10 m 2 / gLi4Ti5O 12 particle.

[0267] (Example 41)

[0268] The positive electrode of Example 1 and the negative electrode of Example 30 were combined, and a secondary battery was produced in the same manner as described in Example 1.

[0269] (Example 42)

[0270] An electrode group was prepared in the same manner as described in Example 30, and the electrode group was housed in a thin metal can similar to the metal can described in Example 1.

[0271] A liquid nonaqueous electrolyte having the same composition as that described in Example 30 was injected into the metal can and allowed to penetrate into the gap between the positive electrode and the negative electrode. Then, the metal can was sealed to obtain a Figure 1 A square nonaqueous electrolyte secondary battery having the structure shown in and the same dimensions as those described in Example 30.

[0272] (Example 43)

[0273] A separator formed of a cellulose fiber nonwoven fabric having a thickness of 20 μm was used instead of the electrolyte containing layer precursor. The positive electrode and the negative electrode were stacked so that the separator was located between the positive electrode active material containing layer and the negative electrode active material containing layer, and wound into a flat spiral shape to produce an electrode group, which was housed in a thin metal can similar to the metal can described in Example 30.

[0274] A liquid nonaqueous electrolyte having the same composition as that described in Example 30 was injected into the metal can and allowed to penetrate into the gap between the positive electrode and the negative electrode. Then, the metal can was sealed to obtain a Figure 1 A square nonaqueous electrolyte secondary battery having the structure shown in and the same dimensions as those described in Example 30.

[0275] The obtained secondary battery was charged to 2.9 V at 25° C. with a constant current of 12 A, then charged at a constant voltage of 2.9 V, and after charging with a current of 0.05 A, the discharge capacity was measured when discharged to 1.5 V with a current of 6 A. After repeating this charge and discharge cycle 5000 times, the capacity retention rate was measured.

[0276] As the high current discharge performance, the capacity retention rate at 5C (30A) discharge was measured (the capacity at 1.2A discharge was set to 100%). Furthermore, the capacity retention rate at 1.2A discharge at -30°C relative to 25°C was measured.

[0277] These measurement results are shown in the following Table 10. In addition, in Table 10, the results of Comparative Example 1 are also shown.

[0278]

Table 7

[0279]

[0280]

Table 8

[0281]

[0282]

Table 9

[0283] Table 9

[0284]

[0285]

Table 10

[0286] Table 10

[0287]

[0288] As shown in Tables 7 to 10, Examples 30 to 43 of the secondary battery have a better balance of cycle life performance, discharge rate performance, and low-temperature discharge performance than Comparative Examples 11 to 16. As shown in the results of Comparative Examples 11 to 16, when the negative electrode contains only one of inorganic solid particles or polymer fibers, the cycle life performance, discharge rate performance, and low-temperature discharge performance are all poor.

[0289] By comparing Example 30 with Example 42, it can be seen that Example 42, which includes a liquid electrolyte instead of a gel electrolyte, has the same cycle life performance as Example 30, and the discharge rate performance and low-temperature discharge performance are also better than Example 30. In addition, by comparing Example 30 with Example 43, it can be seen that Example 30 including a composite electrolyte layer has better cycle life performance, discharge rate performance and low-temperature discharge performance than Example 43 including a separator instead of a composite electrolyte layer. In addition, from the results of Example 41, it can be seen that if both the positive electrode and the negative electrode contain polymer fibers and inorganic solid particles with an average fiber diameter of 1 nm or more and 100 nm or less, the cycle life performance, discharge rate performance and low-temperature discharge performance are all good.

[0290] The electrode according to at least one of these embodiments or examples contains polymer fibers and inorganic solid particles having an average fiber diameter of 1 nm or more and 100 nm or less, thereby reducing the ion conduction resistance in the electrode. Therefore, a secondary battery having the electrode can improve charge and discharge cycle life, discharge rate performance, and low temperature performance.

[0291] It should be noted that several embodiments of the present invention have been described, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These new embodiments can be implemented in various other embodiments, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. These embodiments and their variations are included in the scope and purpose of the invention, and are also included in the invention recorded in the patent claims and their equivalents.

[0292] The invention described in the original patent claims is noted below.

[0293] [1] A positive electrode comprising a positive electrode active material-containing layer, the positive electrode active material-containing layer comprising positive electrode active material particles, polymer fibers having an average fiber diameter of 1 nm to 100 nm, and inorganic solid particles.

[0294] [2] The positive electrode described in [1], wherein the polymer fibers include cellulose fibers.

[0295] [3] The positive electrode described in any one of [1] or [2], wherein the inorganic solid particles contain at least one selected from Al2O3, TiO2, ZrO2 and a phosphoric acid compound.

[0296] [4] The positive electrode described in [3], wherein the phosphate compound has a NASICON structure and is composed of Li 1+ y Al x M 2-x (PO4)3 represents that M is at least one element selected from Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1.

[0297] [5] The positive electrode described in any one of [1] to [4], wherein the content of the polymer fibers in the positive electrode active material containing layer is greater than 0.2 wt% and less than 5 wt%, and the content of the inorganic solid particles in the positive electrode active material containing layer is greater than 0.5 wt% and less than 10 wt%.

[0298] [6] A secondary battery comprising: the positive electrode according to any one of [1] to [5], a negative electrode, and an electrolyte.

[0299] [7] The secondary battery according to [6], wherein the negative electrode comprises an oxide containing titanium.

[0300] [8] The secondary battery according to [7], wherein the titanium-containing oxide comprises at least one selected from spinel-structured lithium titanium oxide, monoclinic titanium oxide, and niobium titanium oxide.

[0301] [9] A battery pack comprising one or more of the secondary batteries described in any one of [6] to [8].

[0302]

[10] The battery pack described in [9] further includes an external terminal for power supply and a protection circuit.

[0303]

[11] The battery pack described in [9] or

[10] comprises two or more of the secondary batteries, wherein the two or more secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.

[0304]

[12] A vehicle equipped with the battery pack according to any one of [9] to

[11] .

[0305]

[13] The vehicle described in

[12] includes a mechanism for converting the kinetic energy of the vehicle into regenerative energy.

Claims

1. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte-containing layer interposed between the positive electrode and the negative electrode, wherein: The negative electrode is an electrode comprising an active material containing layer and a current collector, wherein the active material containing layer comprises active material particles, polymer fibers including cellulose fibers having an average fiber diameter of 1 nm or more and 100 nm or less, and inorganic solid particles. The porosity of the negative electrode excluding the current collector is 20% or more and 50% or less, The inorganic solid particles include at least one selected from Al2O3, TiO2, ZrO2 and a phosphoric acid compound, wherein the phosphoric acid compound has a NASICON structure and is composed of Li 1+y Al x M 2-x (PO4)3 represents that M is at least one element selected from Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1, The electrolyte of the electrolyte-containing layer is a liquid electrolyte or a gel electrolyte. The liquid electrolyte comprises an electrolyte salt and an organic solvent for dissolving the electrolyte salt. The gel electrolyte includes an electrolyte salt, an organic solvent for dissolving the electrolyte salt, and a polymer. The liquid electrolyte or the gel electrolyte is held in a mesh-like space formed by the polymer fiber.

2. The secondary battery according to claim 1, wherein The content of the polymer fibers in the active material-containing layer is 0.2% by weight or more and 5% by weight or less, and the content of the inorganic solid particles in the active material-containing layer is 0.5% by weight or more and 10% by weight or less.

3. The secondary battery according to claim 1 or 2, wherein: The electrolyte-containing layer further includes second inorganic solid particles.

4. The secondary battery according to claim 1 or 2, wherein: The electrolyte-containing layer is a composite electrolyte of second inorganic solid particles and the gel electrolyte.

5. The secondary battery according to claim 4, wherein The ratio of the second inorganic solid particles in the composite electrolyte is greater than or equal to 85 wt % and less than or equal to 98 wt %.

6. The secondary battery according to claim 1 or 2, wherein: The active material containing layer holds the gel electrolyte, and a ratio of the gel electrolyte in the active material containing layer is 1% by weight or more and 10% by weight or less.

7. The secondary battery according to claim 1 or 2, wherein: The active material particles of the negative electrode include an oxide containing titanium.

8. The secondary battery according to claim 7, wherein The titanium-containing oxide includes at least one selected from spinel-structured lithium titanium oxide, monoclinic titanium oxide, and niobium titanium oxide. 9 . A battery pack comprising one or two or more secondary batteries according to claim 1 .

10. The battery pack according to claim 9, further comprising an external terminal for power supply and a protection circuit. 11 . The battery pack according to claim 9 , comprising two or more secondary batteries, wherein the two or more secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.

12. A vehicle equipped with the battery pack according to any one of claims 9 to 11.

13. The vehicle of claim 12, comprising a mechanism for converting kinetic energy of the vehicle into regenerative energy.

Citation Information

Patent Citations

  • Ryutaino isotonyuhoho oyobi sonosochi

    JP1976010565A

  • Wrist device for industrial robot

    JP1985020892A